Predictors of tobacco smoking among youth in an urban slum in Kampala, Uganda: A cross-sectional study - Joyce Nakitende; Anthony Kirabira; Mona Muhammad; Elizabeth Kisembo; Denis Omara; Dennis Kalibbala; Geofrey Musinguzi; Bontle Mbongwe (PLoS ONE, 2026)
Background Tobacco use remains a significant public health concern worldwide. In Uganda, the youth use tobacco at almost three times the rate of adults, with those residing in slum areas exhibiting even higher prevalence levels. Since 2015, strict laws regulating public tobacco use have been implemented in Uganda, however, these measures have not led to a significant decline in tobacco consumption among the youths in slums. Objective To assess the predictors of tobacco smoking among youth living in the slum areas of Kampala, Uganda. Methods This was a cross-sectional study. It was conducted in Bwaise slum in Kampala, we recruited 422 youths aged 18–30 years. Households were sampled systematically, and quantitative data were analyzed using STATA version 14. Modified Poisson regression with robust standard errors was used, prevalence ratios (PR) were used to measure the associations. Factors were considered significant if p-values were less than 0.05. Results The prevalence of current tobacco smoking was 52.6% while the prevalence of ever tobacco smoking was 71.6%. Most of the participants (87.4%) knew the health effects of tobacco use. Gender (adj.PR = 1.74[95% CI = 1.41–2.14]) and age (adj.PR = 1.38[95%CI = 1.10–1.74]) were the strongest predictors of tobacco smoking: the prevalence of tobacco smoking was 74% higher among males compared to females and 38% higher among those aged 21−30 years compared to their younger counterparts. Education level (adj.PR = 0.84[95%CI = 0.70–0.9]), and income/= (adj.PR = 0.79[05%CI = 0.64–0.97) were also predictive of tobacco smoking. Knowledge was also a predictor with prevalence being 34%, 29%, 42% higher among those who didn’t know that smoking causes serious illness (adj.PR = 1.34[95%CI = 1.09–1.64]), stroke (adj.PR = 1.29[95%CI = 1.06–1.59]) and lung cancer (adj.PR = 1.42[95%CI = 1.11–1.83]) respectively. Conclusion More than half of the youth smoke tobacco despite awareness of its health effects. These findings call for development and implementation of targeted initiatives that address the unique needs and behaviors of males, aged 21–30 years, individuals of education below secondary level while addressing the knowledge gaps about effects of tobacco smoking on human health.